Semantic Motivation of Nominative Relatives as a Problem of Modern Lexicograph - N. A. Aksarina; L. V. Basova (Научный диалог)
The question of the semantic motivation of denominative relatives — significant units in the prepositional function is raised in the article. The influence on the volume and structure of the lexical part of the meaning of denominative relatives and their adverbial homonyms of the same semes inherited from the deriving name is comprehended. Peculiarities of semantization of adverbial and prepositional meanings are considered on the examples of relatives as a result and bypassing. It is proved that the ambiguity of ideas about semantic motivation largely determines the non-systematic fixation of homonymous service and significant units in dictionaries: adverbs are interpreted mainly through only one synonym and do not have a descriptive component in the definition, while prepositions are characterized by more detailed descriptive-synonymous definitions, including at least two partial synonyms. The analysis of dictionary entries and materials of the National Corpus of the Russian allows us to conclude that denominative relatives have a more complexly organized lexical part of the meaning than homonymous adverbs with the same generating base. It has been established that with the expansion of the system of meanings of a service language unit, there is a simplification of the seme composition of each individual meaning.